HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG PENYAKIT DERMATITIS ATOPIK DENGAN KEJADIAN KEKAMBUHAN DERMATITIS ATOPIK PADA ANAK DI POLI KULIT RUMAHSAKIT TOTO KABUPATEN BONE BOLANGO - Mohammad Hadi; Andi Akifa Sudirman (-, 2021)
Atopic dermatitis is the most common in infants, but can also in children and adults. In most patients, the clinical manifestations of atopic dermatitis is atopic that first, and then many of them will have asthma and allergic rhinitis. Although genetic predisposition is one of the most important risk factor, but the increasing prevalence of atopic dermatitis in industrialized countries suggests that environmental factors (exposure to microbes and nutrients) also has an important role. The purpose of this study was to determine the level of knowledge mother Relations About Diseases Atopic Dermatitis Atopic Dermatitis With Genesis Relapse In Children In Poly Leather District Hospital Bone Toto Bolango. The study design used was a descriptive cross-sectional design. Population and sample are all mothers who bring their children with a mother who was 26, totaling 26 samples mother. Sampling technique Consecutive Sampling Techniques. Analysis carried out in stages (1) Univariate analysis using frequency distribution. (2) Bivariate analysis to examine the relationship between variables by using statistical analysis of test chi - square, in order to determine the relationship of the study variables with a significance value (p value) <0.05 or (5%). Statistical test results obtained by the value of p = 0.006 (p <0.05) and the odds ratio value of 18 means There Relationship Between Mothers Knowledge About Diseases Atopic Dermatitis Atopic Dermatitis With Genesis Relapse In Children's Hospital In Poly LeatherToto. As donations applicable to nurses, in order to improve the provision of care services, especially health education to mothers about the relationship of knowledge with atopic dermatitis recurrence so that they can perform better penangnan to the child / family.